Educação profissional tecnológica de graduação: contribuições à luz da pedagogia do sujeito - Molitor, Simone Cristina Gonçalves Vianna (2011)
This work aimed to study the relationship between the educational process of professional "training" and the demands required for the world of work. The technological professional education of graduate, known in Brazil, as higher technological graduation, despite the strong link with the world of work, does not adequately prepare professionals who attend to their demands. This documental research looks for to contemplate the government's proposals for the technological professional education of graduate in the brazilian Education. With an hermeneutica approach, I interpret proposals, progress and setbacks of the brazilian professional education. The results of this investigation show the fragility of the speeches in official documents and show signs of a proposal focused on temporal answering of the demands of labor markets and not of the worker. Thus, I seek to understand the needs of the world work and the changes occurred in this universe, especially with regard to the evolution of techno and its impact on the technological professional education of graduate. Faced with the conceptions found, the present study, supported by the Pedagogy of the subject, shows that it is not enough for the technological professional education of graduate to "train" professionals, but rather help and as well as contribute they may recognize themselves and build themselves subjects